HISTOLOGICAL PROFILE OF THE SMALL INTESTINE OF SASSO CHICKEN FED DIETS WITH SUN-DRIED TARO PLANT - Berbano, Quennie (International Journal of Arts, Sciences and Education, 2024)
ABSTRACT This study aimed to evaluate the effects of incorporating the Sun-Dried Taro Plant (SDTP) into the histological profile of small intestine of Sasso chicken at a dietary level of 0%, 3%, 6, 9% and 12% respectively. The study was conducted at the ASC Agriculture Demonstration Farm and Laboratory at San Gregorio Luna, Apayao from September 16, 2023 to November 16, 2023. A total of one hundred fifty (150) two-week-old Sasso chicks were assigned in a Completely Randomized Design with three replications. Based on the result of the study, the dietary supplementation of sun-dried taro plant revealed a trend of shortened villi in the duodenum and ileum with higher sun-dried taro plant (SDTP) levels, but only the ileum showed a statistically significant difference in crypt depth compared to the control. The result is in congruence to final body weight, gain in weight and FCR. The inclusion of the sun-dried taro plant on the production performance of Sasso chicken shows no significant effect on the final body weight, total gain in weight, cumulative feed consumption, FCR and FCE. The use of sun-dried taro plant is safe as feed ingredient, hence recommended. The taro plant can be included in the Sasso chicken diet without negative effect on their health performance. However, further research is needed to fully understand the potential benefits and drawbacks of higher SDTP levels on chicken health and intestinal function.